2016
DOI: 10.9758/cpn.2016.14.4.357
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Equine-assisted Activities and Therapy on Resting-state Brain Function in Attention-deficit/Hyperactivity Disorder: A Pilot Study

Abstract: ObjectiveEquine-assisted activities and therapy (EAA/T) have been used as adjunct treatment options for physical and psychosocial rehabilitation. However, the therapeutic effects on resting-state brain function have not yet been studied. The aim of this study is to investigate the effects of EAA/T on participants with attention-deficit/hyperactivity disorder (ADHD) by comparing resting-state functional magnetic resonance imaging (rs-fMRI) signals and their clinical correlates.MethodsTen participants with ADHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…Twenty‐six studies found functional/behavioural improvement after the implemented rehabilitation interventions; however, one study examining the effects of cognitive training on children with ADHD did not find any functional or behavioural improvements (Hoekzema et al, 2011). Eleven studies reported a positive relationship between improvements in rehabilitation‐induced brain plasticity and behavioural measures (Manning et al, 2016; Murdaugh et al, 2016, 2015; Soh et al, 2015; Chaturvedi et al, 2013; You et al, 2005; Kim et al, 2015; Hoekzema et al, 2011; Englander et al, 2015; Sterling et al, 2013; Yoo et al, 2016). In what follows, we review and tabulate the results by studied MRI outcomes: structural connectivity, functional connectivity, cortical activation, and structural volume .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐six studies found functional/behavioural improvement after the implemented rehabilitation interventions; however, one study examining the effects of cognitive training on children with ADHD did not find any functional or behavioural improvements (Hoekzema et al, 2011). Eleven studies reported a positive relationship between improvements in rehabilitation‐induced brain plasticity and behavioural measures (Manning et al, 2016; Murdaugh et al, 2016, 2015; Soh et al, 2015; Chaturvedi et al, 2013; You et al, 2005; Kim et al, 2015; Hoekzema et al, 2011; Englander et al, 2015; Sterling et al, 2013; Yoo et al, 2016). In what follows, we review and tabulate the results by studied MRI outcomes: structural connectivity, functional connectivity, cortical activation, and structural volume .…”
Section: Resultsmentioning
confidence: 99%
“…In children with CP, a 3‐week CIMT intervention induced a more balanced resting state network, which correlated with functional capacity of the hemiplegic hand (Manning et al, 2016). Equine‐assisted therapy reduced ADHD symptoms after 12 weeks, which correlated with improved functional connectivity in the right precuneus and pars orbitalis (Yoo et al, 2016). The only strong‐quality study investigated functional connectivity in children with ASD and showed that 10 weeks of visualizing and verbalizing for language comprehension and thinking intervention increased reading comprehension abilities, which correlated with greater connectivity in Broca's and Wernicke's area (Murdaugh et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition one pilot study has been undertaken looking at the effects of EAIs and therapy on resting brain state function in attention-deficit/hyperactivity disorder [32]. This study found that the intervention was associated with short range functional connectivity in the regions of the brain related to the behavioural inhibition system, which are associated with symptom improvement in this group.…”
Section: Background To Equine Assisted Interventions (Eais)mentioning
confidence: 99%